2015
DOI: 10.1093/eurpub/cku234
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in hazardous drinking among middle-aged in Europe: the role of social context and women’s empowerment

Abstract: Background:The aim of this study was to estimate the magnitude of gender differences in hazardous drinking among middle-aged people and to analyse whether these differences are associated with contextual factors, such as public policies or socioeconomic factors. Methods: Cross-sectional design. The study population included 50-to 64-year-old residents of 16 European countries who participated in the Survey of Health, Ageing and Retirement in Europe project conducted in 2010-12 (n = 26 017). We estimated gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 34 publications
8
47
0
4
Order By: Relevance
“…These huge variations between countries are consistent with estimates from a previous study with country-level data including all adults (Shield et al, 2013). As expected, the prevalence of hazardous drinking was higher in men than women, in line with previous studies, which showed that not only was the frequency of alcohol consumption higher in men, but also the prevalence of risky drinking patterns such as hazardous or binge drinking (Bosque-Prous et al, 2015;Mäkelä et al, 2006;Wilsnack et al, 2009). As an example, prevalence of hazardous drinking in U.S. older people was estimated around 10% (Blazer and Wu, 2009;Merrick et al, 2008).…”
Section: Hazardous Drinking In Europe In People Aged 50 or Oldersupporting
confidence: 92%
See 3 more Smart Citations
“…These huge variations between countries are consistent with estimates from a previous study with country-level data including all adults (Shield et al, 2013). As expected, the prevalence of hazardous drinking was higher in men than women, in line with previous studies, which showed that not only was the frequency of alcohol consumption higher in men, but also the prevalence of risky drinking patterns such as hazardous or binge drinking (Bosque-Prous et al, 2015;Mäkelä et al, 2006;Wilsnack et al, 2009). As an example, prevalence of hazardous drinking in U.S. older people was estimated around 10% (Blazer and Wu, 2009;Merrick et al, 2008).…”
Section: Hazardous Drinking In Europe In People Aged 50 or Oldersupporting
confidence: 92%
“…To choose the variables at the country level, we take into account a conceptual framework of gender differences in alcohol consumption (Bosque-Prous et al, 2015) adapted from two frameworks of social determinants of health (Comisión Para Reducir Las Desigualdades Sociales En Salud En España, 2012; Solar and Irwin, 2007). The variables of that framework which have been suggested to be related with alcohol consumption in people aged ≥50 years and, thus, were included in this study were: (a) standardized national unemployment rate in people aged 15-64 years (Organisation for Economic Co-operation and Development, 2015); (b) standardized Gross Domestic Product per head (European Commission, 2015); (c) standardized Gender Inequality Index (United Nations Development Programme, 2015), which reflects gender-based disadvantages in three dimensions (reproductive health, empowerment and the labour market).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…16, 108 109 Men´s health seem to be more likely to be affected by "risky" behaviour such as smoking or drinking alcohol, 83,110,111 whereas women´s health is influenced by more structural and psychosocial factors. 112,113 However, sex discrimination in health-care expenditure with a consequent survival advantage for men is well-known in some countries, 67, 114 so much so that female patients assess the quality of their hospital care significantly worse than do male patients, and call for better nursing care and better management of their pain.…”
Section: Medical Interventionsmentioning
confidence: 99%